Current sharing and stability in an extremely low AC-loss MgB2 conductor. Issue 1 (1st May 2022) - Kovacs, C J; Haugan, T J; Sumption, M D; Tomsic, M; Rindfleisch, M
Abstract: In the push to develop high power electric aircraft, superconducting technology promises to significantly reduce mass and volume of motors and generators. However, challenges related to AC-loss and thermal management are a significant factor in preventing the proliferation of aerospace superconducting technologies. Increasing the resistance of the metal matrix stabilization has only gone so far in reducing coupling currents for higher frequency applications. In this research, Multiphysics simulations of a single composite filament were used to investigate stability decreases when using very high thermal conductivity electrical insulator (CsI) or metal-to-insulator transitioning material (V2 O3 ) to replace the slightly resistive metal matrix typically used for a low AC loss MgB2 composite wire. The insulators separate the MgB2 filaments entirely, only allowing transient current sharing to occur with the high purity Nb diffusion barrier or with the metallic state V2 O3 . These simulations show that for these very low AC-loss composites at 20 K, instability will become a major issue due to reductions in current sharing. With higher electrical conductivity metal-to-insulator materials, higher thermal conductivity impregnation materials, and thicker metallic diffusion barriers it may be possible to find a reasonable balance between AC-loss and stability.